Sakrale Neuromodulation - Matzel, Klaus E.; Bittorf, B. (Coloproctology, 2020)
Over the last few years sacral neuromodulation has evolved to become the mainstay of surgical treatment of fecal incontinence. The electrode positioning is the crucial element of the operative intervention. With suboptimal electrode placement the probability of treatment success is reduced, the risk of negative side effects is increased and the energy consumption of the stimulation is increased resulting in reduced longevity of the battery and higher treatment costs. Preliminary findings indicate that the modified technique of electrode placement using intraoperative imaging and a curved stylet leads to better electrode positioning. The modified technique of electrode placement in sacral neuromodulation enables a more precise and effective treatment.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Curved stylets; Electrode placement; Fecal incontinence; Sacral spinal nerve stimulation; Tined lead electrode